Efforts to Instill Character Values through Habituation of Memorization of Hadith in KB IT Ash Shiddiqy Kalimatan Jepara - Tarjiati, Ita Tara; Zulfahmi, Muhammad Nofan (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2024)
Character education in early childhood is one of the efforts to instill commendable behavior in children, both in worship, both as citizens, both in interacting with others and the environment, and beneficial for the success of their lives both in the world and in the hereafter. The purpose of this study is to determine the values of character education instilled in children aged 3-4 years through habituation of memorization of selected hadiths in KB IT Ash Shiddiqy. This research method uses descriptive qualitative. The subjects in this study were 10 children aged 3-4 years Abu Bakr group at KB IT Ash Shiddiqy as the main informant in this study. Data collection techniques in research use observation, interview and documentation techniques. The result of this study is that children can be formed in character from the age of 3-4 years through habituation to memorizing hadiths prohibiting anger, affection, smiles, closing the aurat, and brotherhood.